Design and Evaluation of a Heat Exchanger That Uses Paraffin Wax and Recycled Materials as Solar Energy Accumulator - Reyes-Salinas, A; Sepulveda-Palma, F; Mahn-Osses, A (Elsevier Ltd, 2014)
Soft drink cans filled with paraffin wax mixed with 5% w/w aluminum wool, obtained from disposable cans, doubled the thermal conductivity of cans filled only with paraffin wax. Thermal conductivity of the systems was determined by two ways: directly using a thermal conductivimeter, and indirectly based on temperature profiles and on the analytical solution of a cylinder. We designed, built and evaluated a heat exchanger for solar energy accumulation, composed by 48 disposable soft drink cans filled with a total of 9.5 kg of paraffin wax mixed with 5% w/w aluminum wool. In sunny days, the wax melted completely in 3 h. The accumulated energy of 3000 kJ, allowed increasing the temperature of 3.5 m3/h air flow rate from 20 to 40 °C during a period of 2 h. This application will allow extending the use of solar energy in drying processes or could be used as household calefaction system. The progress of the phase change front in time during the energy discharge period was simulated with COMSOL, whereas the effect of the number of cans and thermal conductivity of the paraffin wax on the air temperature increase was simulated with MATLAB. © 2014 Elsevier Ltd. All rights reserved.